Cell Death Signaling From Endoplasmic Reticulum Stress: Plant-Specific and Conserved Features - Simoni, Eduardo B.; Oliveira, Célio C.; Fraga, Otto T.; Reis, Pedro A. B.; Fontes, Elizabeth P. B. (Frontiers in Plant Science, 2022)
The endoplasmic reticulum (ER) stress response is triggered by any condition that disrupts protein folding and promotes the accumulation of unfolded proteins in the lumen of the organelle. In eukaryotic cells, the evolutionarily conserved unfolded protein response (UPR) is activated to clear unfolded proteins and restore ER homeostasis. The recovery from ER stress is accomplished by decreasing protein translation and loading into the organelle, increasing the ER protein processing capacity and ER-associated protein degradation activity. However, if the ER stress persists and cannot be reversed, the chronically prolonged stress leads to cellular dysfunction that activates cell death signaling as an ultimate attempt to survive. Accumulating evidence implicates ER stress-induced cell death signaling pathways as significant contributors for stress adaptation in plants, making modulators of ER stress pathways potentially attractive targets for stress tolerance engineering. Here, we summarize recent advances in understanding plant-specific molecular mechanisms that elicit cell death signaling from ER stress. We also highlight the conserved features of ER stress-induced cell death signaling in plants shared by eukaryotic cells.